Peran Kepala Ruangan dalam Peningkatan Kepuasan Kerja Perawat - Yosephine Br Sitepu (Lembaga Pengembangan Kinerja Dosen, 2026)
Continuous changes in society and its environment require the nursing profession to adapt and evolve. Nursing, as an integral part of society, will become irrelevant if it does not renew itself in terms of managing and organizing its professional life. This study aims to analyze the influence of the role of the head nurse on the performance of nurses in providing nursing care. The research method used is an analytical survey with a cross-sectional approach. Data collection was carried out using a questionnaire, then analyzed with a linear regression test at a significance level of α < 0.05. The results of the analysis show that the role of the ward head has an influence on the performance of practicing nurses in providing nursing care, which includes the functions of planning (ρ = 0.007), organizing (ρ = 0.005), directing (ρ = 0.008), and supervising (ρ = 0.006). These findings indicate that the managerial functions of the ward head play an important role in supporting the improvement of the performance of practicing nurses. Therefore, it is necessary to improve the managerial skills of ward heads in managing nursing services, provide ward management training for ward heads who do not yet have certification, and develop a competency-based ward head selection and appointment policy.